PERBEDAAN KADAR TIMBAL (Pb) DALAM DARAH BERDASARKAN JENIS PEKERJAAN PADA PEKERJA INDUSTRI PENGECORAN LOGAM DI CV. BONJOR JAYA, CEPER, KLATEN - Vifta Dian Lestari; Onny Setiani; Niki Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Metal foundry industry workers is one of the people who are at risk of lead exposure as the effect of air pollution by lead in workplace. These workers are exposed to lead every day as a result of their activities likes melting, stamping, and finishing process at this industry. The aim of the research is to know the difference about blood lead level in workers at the melting section, stamping section and finishing section in CV. Bonjor Jaya, Ceper, Klaten. This observational research with a cross sectional approach. The population is 34 workers in CV. Bonjor Jaya and 31 sample selected by purposive sampling method. Data analysis is done by using Krusskal Wallis test with significance value 5%. Result showed that air lead levels in each section are 0,208 mg/Nm3(melting), 0,212 mg/Nm3(stamping) and 0,037 mg/Nm3(finishing) as well as the average of blood lead level in workers at the each section are 15,97 µg/l (melting), 18,10 µg/l (stamping) and 10,54 µg/l (finishing). Based on statistic analysis was known that p value = 0,320 with α 0,05, this result show that there is no significant difference of blood lead level based on type of work in metal foundry workers in CV. Bonjor Jaya, Ceper, Klaten. Based on this research concluded that average of blood lead level on workers are above normal (CDC=10 μg/dl). Suggestion for metal foundry industry workers to always use a standard mask to reducing lead exposure in the body.